Pendampingan Motivasi dan Spiritual Emosional Frequency Therapy (SEFT) untuk Lansia di Kelurahan Bandungrejosari, Sukun, Malang - Made Iska Aprilita Wardani; Kristin Juwita; Sarlotha Selan; ABD Ghofar; Ainur Rahim Setiawan (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Elderly people are individuals aged 60 and over who have equal rights in community life. The emotional state of the elderly is a psychological state that encompasses the ability to think, feel, and act, as manifested through behavior. To stabilize the emotions of the elderly, cadres and their families must have an adequate level of emotional intelligence. One non-pharmacological approach currently being studied is the Spiritual Emotional Freedom Technique (SEFT), an emotional healing method that combines spiritual elements, positive affirmations, and stimulation of the body's meridian points. SEFT is believed to reduce psychological stress that contributes to high blood pressure. This therapy is easy to learn, can be performed independently, and requires no special equipment, making it highly suitable for use in elderly communities with limited access to advanced medical services. At this event, counselors provided support in delivering material on Motivation and Prevention of Psychological Disorders in the Elderly using the SEFT. The purpose of this material is to provide motivation, reduce, and prevent psychological impacts. Participants benefited from the material, knowledge, and experience sharing, as well as solutions, resulting in a better understanding of motivation, reduction, and prevention of psychological impacts. This community service program was conducted with approximately 33 participants in the "Teratai" elderly group. It is hoped that this community service program will be beneficial and provide considerations for solutions and decisions, adding information and insight related to motivation, reduction, and prevention of psychological impacts.